2000
DOI: 10.1037/h0087330
|View full text |Cite
|
Sign up to set email alerts
|

Home literacy activities and their influence on early literacy skills.

Abstract: The relationship between the home environments of 66 children and their language and literacy development was examined. After accounting for child age, parent education, and child ability as indexed by scores on a rapid automatized naming task and Block Design of the WPPSI-R, shared book reading at home made no contribution to the prediction of the literacy skills of letter name and letter sound knowledge in kindergarten. In contrast, home activities involving letters predicted modest and statistically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
244
4
22

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(306 citation statements)
references
References 55 publications
(61 reference statements)
26
244
4
22
Order By: Relevance
“…In other words, once the frequency of home reading and children's background characteristics were held constant, children whose parents taught them more frequently at home tended to have lower average scores at the end of the study in phonological awareness, vocabulary, word reading, and pseudoword reading in Korean. These results differ from previous findings with Englishspeaking and French-speaking families (Evans, Shaw, & Bell, 2000;Sénéchal 2006a;Sénéchal et al, 1998) and from the results of a meta-analysis of home teaching intervention studies, which revealed positive effects of parent teaching on children's emergent literacy and conventional literacy skills (Sénéchal, 2006b). …”
Section: Discussioncontrasting
confidence: 99%
“…In other words, once the frequency of home reading and children's background characteristics were held constant, children whose parents taught them more frequently at home tended to have lower average scores at the end of the study in phonological awareness, vocabulary, word reading, and pseudoword reading in Korean. These results differ from previous findings with Englishspeaking and French-speaking families (Evans, Shaw, & Bell, 2000;Sénéchal 2006a;Sénéchal et al, 1998) and from the results of a meta-analysis of home teaching intervention studies, which revealed positive effects of parent teaching on children's emergent literacy and conventional literacy skills (Sénéchal, 2006b). …”
Section: Discussioncontrasting
confidence: 99%
“…The predictive role of parental teaching of literacy on children’s reading/spelling skills at or around school entry has been reported in numerous studies from various countries (Evans et al, 2000; Foy & Mann, 2003; Manolitsis et al, 2013; Martini & Sénéchal, 2012). This “formal” aspect of home literacy has also been reported to be independent of informal home-based literacy activities (Phillips & Lonigan, 2009; Sénéchal & LeFevre, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, once young children have begun to acquire the alphabetic principle, shared storybook reading can provide a facilitative context for the development of code-based emergent literacy skills (Mol, Bus, & de Jong, 2009). Together these sorts of findings may explain inconsistencies in the literature, which reports both positive (Evans, Shaw, & Bell, 2000; Hood, Conlon, & Andrews, 2008; Senechal & Lefevre, 2002) and negative (Sénéchal & Lefevre, 2014; Silinskas et al, 2012) associations between parental teaching and children’s early literacy skills.…”
mentioning
confidence: 97%
“…Significant factors were parents' education and occupation, house building material and domestic facilities. In earlier studies, parents' education and occupation have also been significantly related to children's literacy skills (Bowey, 2005;Evans et al, 2000;Ortiz, 2000). It is obvious that parents engaged in professional jobs have attained a good level of education and income to support their children's literacy development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that children's exposure to literacy-related activities at home (e.g. story book reading, visits to the library, parental involvement in teaching children to read and write etc) is important for children's phonological awareness and reading and writing ability (Burgess 2002;Evans et al, 2000;Foy, 2003;Neumann et al, 2009;Roberts et al, 2005). Moreover, parents' education, and especially mothers' education, has been shown to significantly contribute to children's reading and writing ability (Jariene & Razmantiene, 2006).…”
Section: Home Environment In Relation To Phonological Awareness and Rmentioning
confidence: 99%